Pemanfaatan Robot Berbasis AI untuk Pemantauan dan Respon Bencana Alam - Manisa, Bunga Nurul; Desmarini, Mutia; Lubis, M. Luthfi; Rahman, Aulia; Pratama, Putra; Akbar, M. Rabbani (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This research discusses the utilization of artificial intelligence (AI)-based robots in monitoring and responding to natural disasters in Indonesia. Disasters such as earthquakes, floods, and forest fires demand rapid and effective handling, yet they are often hindered by difficult terrain and safety risks. Robotics and AI emerge as innovative solutions, enabling automated navigation, object detection, and real-time data collection in hazardous environments. This study aims to explore the use of AI robots in disaster management, employing a literature review methodology that identifies the challenges and opportunities in their application. The results indicate that robots can enhance the efficiency and safety of rescue teams, although there are still challenges related to battery life and communication infrastructure. Proposed solutions include the development of more efficient batteries and the integration of advanced technologies to improve operational effectiveness. This research is expected to serve as a foundation for the development of more adaptive and efficient robots in natural disaster situations.